Serum Levels of IL-1β, IL-6, TGF-β, and MMP-9 in Patients Undergoing Carotid Artery Stenting and Regulation of MMP-9 in a New In Vitro Model of THP-1 Cells Activated by Stenting - Rongrong Zhang; Fan Jiang; Cindy Si Chen; Tianzhu Wang; Jinzhou Feng; Tao Tao; Xinyue Qin (Mediators of Inflammation)
Inflammation plays an important role in the pathophysiological process after carotid artery stenting (CAS). Monocyte is a significant source of inflammatory cytokines in vascular remodeling. Telmisartan could reduce inflammation. In our study, we first found that, after CAS, the serum IL-1β, IL-6, TGF-β, and MMP-9 levels were significantly increased, but only MMP-9 level was elevated no less than 3 months. Second, we established a new in vitro model, where THP-1 monocytes were treated with the supernatants of human umbilical vein endothelial cells (HUVECs) that were scratched by pipette tips, which mimics monocytes activated by mechanical injury of stenting. The treatment enhanced THP-1 cell adhesion, migration and invasion ability, and the phosphorylation of ERK1/2 and Elk-1 and MMP-9 expression were significantly increased. THP-1 cells pretreated with PD98095 (ERK1/2 inhibitor) attenuated the phosphorylation of ERK1/2 and Elk-1 and upregulation of MMP-9, while pretreatment with telmisartan merely decreased the phosphorylation of Elk-1 and MMP-9 expression. These results suggested that IL-1β, IL-6, TGF-β, and MMP-9 participate in the pathophysiological process after CAS. Our new in vitro model mimics monocytes activated by stenting. MMP-9 expression could be regulated through ERK1/2/Elk-1 pathway, and the protective effects of telmisartan after stenting are partly attributed to its MMP-9 inhibition effects via suppression of Elk-1.